OPTIMATION TIME PRODUCTION SECONDARY METABOLITES ENDOFIT BACTERIES EXTRACT OF PUCUK MERAH LEAVES (Syzygium myrtifolium Walp.) - Rahimah, Priliza; Astuti, Winni; Marliana, Eva (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Pucuk Merah (Syzygium myrtifolium Walp.) is an ornamental plant that has benefits as an antioxidant, antibacterial, antiplatelet, antiulcerative, antimalarial, antiviral, antihyperglycemic and anti-inflammatory. This research aims to determine the optimum time for the production of secondary metabolites of pucuk merah endophytic bacteria for amylase and protease inhibition. Production of secondary metabolites was carried out at various times of 24 hours, 48 ​​hours and 72 hours. The method for the amylase inhibition test used the DNS method and the protease inhibition test used the Bradford method. The results showed that the optimum time for the production of secondary metabolites was 48 hours. Keywords: Syzygium myrtifolium Walp., Endophyte Bacteria, Production Time.